Studying Huntington’s Disease in Yeast: From Mechanisms to Pharmacological Approaches - Hofer, Sebastian; Kainz, Katharina; Zimmermann, Andreas; Bauer, Maria A.; Pendl, Tobias; Poglitsch, Michael; Madeo, Frank; Carmona-Gutierrez, Didac (Frontiers in Molecular Neuroscience, 2018)
Huntington’s disease (HD) is a neurodegenerative disorder that leads to progressive neuronal loss, provoking impaired motor control, cognitive decline, and dementia. So far, HD remains incurable, and available drugs are effective only for symptomatic management. HD is caused by a mutant form of the huntingtin protein, which harbors an elongated polyglutamine domain and is highly prone to aggregation. However, many aspects underlying the cytotoxicity of mutant huntingtin (mHTT) remain elusive, hindering the efficient development of applicable interventions to counteract HD. An important strategy to obtain molecular insights into human disorders in general is the use of eukaryotic model organisms, which are easy to genetically manipulate and display a high degree of conservation regarding disease-relevant cellular processes. The budding yeast Saccharomyces cerevisiae has a long-standing and successful history in modeling a plethora of human maladies and has recently emerged as an effective tool to study neurodegenerative disorders, including HD. Here, we summarize some of the most important contributions of yeast to HD research, specifically concerning the elucidation of mechanistic features of mHTT cytotoxicity and the potential of yeast as a platform to screen for pharmacological agents against HD.